SAT0356 The Therapeutic Efficacy of the Novel Uricosuric Agent UR-1102 for Hyperuricemia and Gout. (23rd January 2014) - Ahn, S. O.; Horiba, N.; Ohtomo, S.; Lee, K. J.; Kim, K. H.; Kim, B. H.; Kiyokawa, J.; Yamane, M.; Ikegami, H.; Nakagawa, T.; Hwang, H.-H.; Park, J.-H.; et al.
Abstract : Background: Control of blood uric acid is important for the treatment of gout. The clinical potential of a selective uric acid transporter 1 (URAT1) inhibitor as a drug for hyperuricemia and gout remains unknown because currently available uricosuric drugs block renal uric acid reabsorption by inhibiting not only URAT1 but also other transporters responsible for renal tubular uric acid secretion, such as OAT1 or OAT3. We have identified a highly selective URAT1 inhibitor, UR-1102, which is now under clinical trial for gout. Objectives: In this study, we examined the therapeutic potential of selective URAT1 inhibition with UR-1102 by comparing it with benzbromarone, a traditional non-selective URAT1 inhibitor, in vitro and in vivo with cebus monkeys, an animal model that has similar purine metabolism and urinary uric acid excretion to humans. Methods: The inhibitory effects of UR-1102 and benzbromarone on URAT1, OAT1, OAT3 and ABCG2 were evaluated in vitro using CHO cells that over-express these transporters. UR-1102 at 3, 10, and 30 mg/kg or benzbromarone at 3, 10, 30, and 100 mg/kg were administered orally once a day to cebus monkeys for 3 consecutive days ( n =6, cross-over study). Plasma and urinary excretion of uric acid and creatinine were measured at regular time intervals. Fractional excretion of uric acid (FEUA) was calculated from those values. Results: UR-1102 exhibited significantly more potent and highly selective (Ki values for URAT1 were >100 smaller than other transporters) URAT1 inhibition than benzbromarone in vitro, while benzbromarone inhibited URAT1, OAT1, OAT3 and ABCG2 dose-dependently as reported in the literature. The average plasma uric acid concentration for the control group was 3.6 +/- 0.2 mg/dL and FEUA was 8.8% +/- 0.4% on day 3 (0–8 hours after 3 rd administration) in the cebus monkeys. Benzbromarone showed dose-dependent and significant reduction of plasma uric acid concentration (3.4, 3.0, 2.8, and 2.7 mg/dL at 3, 10, 30, and 100 mg/kg, respectively) and increase of FEUA (10.3%, 14.5%, 18.5%, and 20.6% at 3, 10, 30, and 100 mg/kg, respectively). UR-1102 also showed the dose-dependent and significant effects on plasma uric acid reduction (2.5, 2.4, and 1.8 mg/dL at 3, 10, and 30 mg/kg, respectively) and increase of FEUA (22.6%, 35.4%, and 42.1% at 3, 10, and 30 mg/kg, respectively). The effects were more apparent for UR-1102 at a lower dose. Moreover, comparing the submaximal dose of UR-1102 at 30 mg/kg with benzbromarone at 100 mg/kg, the effects were significantly higher for UR-1102 than for benzbromarone (plasma uric acid concentration: 1.8 +/- 0.2 mg/dL vs 2.7 +/- 0.2 mg/dL, p<0.01 and FEUA: 42.1% +/- 4.4% vs 20.6% +/- 2.3%, p<0.05). Conclusions: Hypouricemic and uricosuric effects were more potent for UR-1102 than for benzbromarone in both dose and maximum efficacy in cebus monkeys. This may be due to the high selectivity of UR-1102 for URAT1. UR-1102 would have greater efficacy as a therapeutic drug for gout/hyperuricemia than benzbromarone. Disclosure of Interest: S. O. Ahn Employee of: C&C Research Laboratories, N. Horiba Employee of: Chugai Pharmaceutical Co., Ltd., S. Ohtomo Employee of: Chugai Pharmaceutical Co., Ltd., K. J. Lee Employee of: C&C Research Laboratories, K. H. Kim Employee of: C&C Research Laboratories, B. H. Kim Employee of: C&C Research Laboratories, J. Kiyokawa Employee of: Chugai Pharmaceutical Co., Ltd., M. Yamane Employee of: Chugai Pharmaceutical Co., Ltd., H. Ikegami Employee of: Chugai Pharmaceutical Co., Ltd., T. Nakagawa Employee of: Chugai Pharmaceutical Co., Ltd., H.-H. Hwang Employee of: JW Pharmaceutical corp., J.-H. PARK Employee of: JW Pharmaceutical corp., J. Y. Cha Employee of: JW Pharmaceutical corp., J. Tanaka Employee of: Shin Nippon Biomedical Laboratories, Ltd., T. Kake Employee of: Chugai Pharmaceutical Co., Ltd.